Efficacy and Safety of Prothrombin complex Concentrate in Patients with Massive Intraoperative Bleeding During non-Cardiac Surgery: A Retrospective Cohort Study - Bo Tang MD; Yuelun Zhang PhD; Jia Gan MD; Lulu Ma MD; Yuguang Huang MD (Clinical and Applied Thrombosis/Hemostasis, 2025)
Purpose The efficacy and safety of four-factor prothrombin complex concentrate (4F-PCC) in managing bleeding during non-cardiac surgery are unclear. We investigated the associations of 4F-PCC with postoperative RBC transfusion and adverse events in non-cardiac surgery patients with massive intraoperative bleeding. Methods This retrospective cohort study consecutively included non-cardiac surgery patients with massive intraoperative bleeding at a tertiary hospital (2014–2020). Administration of 4F-PCC was categorized into dose groups based on quartiles: 0 (reference), 2.8–6.7, 6.7–11.5, 11.5–19.4, and 19.4–87.5 IU/kg. Outcomes included postoperative RBC transfusion, major thromboembolic events, severe acute kidney injury, and lengths of ICU and hospital stay. Results Of 137 patients, 89 (65.0%) received 4F-PCC. The 6.7–11.5 IU/kg group were significantly associated with reduced postoperative RBC transfusion compared to the non–4F-PCC group (adjusted mean difference, −1.29 units; 95%CI, −2.55 to −0.04 units, P  = 0.044). Such findings were not observed in other dose groups. Notably, the benefits were particularly significant in patients with preoperative platelet count ≥150 × 109/l ( P  = 0.031), and fibrinogen ≥3 g/l ( P  = 0.025). The 6.7–11.5 IU/kg group exhibited comparable incidences of major thromboembolic events (13.0% vs 10.4%) and severe acute kidney injury (8.7% vs 8.3%) compared to the non–4F-PCC group. The lengths of ICU and hospital stay were similar across groups. Conclusion 4F-PCC may be associated with decreased postoperative RBC transfusion in non-cardiac surgery patients experiencing massive intraoperative bleeding, without a significant increase in the risk of major thromboembolic events. Randomized trials with stratified dosing are warranted to confirm efficacy, safety, and determine optimal doses. Clinical Trial Number ChiCTR2500096573.